Amplifying Female Voices in Pakistani Primetime Drama: A Cultural Feminist Analysis of the Drama Serial ’Udaari’ - Dua Saud; Usama Javed Iqbal (JELLL, 2025)
In Pakistan, women and children are victimized frequently by the patriarchal structure. The worst manifestation of this abuse is sexual offense against women and children whose mal-treatment has become the integral part of South Asian culture. This research unveils the sexual abuse against women and children in Pakistan through cultural feminist perspective which highlights the inequalities and disparities women face in patriarchal societies. It also tries to critically analyze the Urdu drama serial Udaari’s role in women’s empowerment and explores awareness against sexual violence to showcase strong Pakistani female characters who stand against sexual violence and patriarchy in society It also unveils the caring nature of women who contribute for the development and harmony in the society. The results of this research show that despite being a part of patriarchal society, women direly scuffle to take a stand for their basic fundamental rights. They expose the abusers and instead of considering themselves as victims, they consider themselves as survivors. Furthermore, it also highlights that when survivors and their family take a firm stand against the sexual abuse, it becomes inevitable for the judiciary to provide justice to the oppressed women. This drama also concludes that despite several challenges in the judicial system, the judicial system in Pakistan can still be trusted to seek justice for women in the society.